Menentukan Potensi Resiko Kanker pada Pemeriksaan CT Scan Toraks dengan Metode SSED - Gusti Ngurah Sutapa; Ni Putu Aprillia Artanti Phalosa; I Wayan Balik Sudarsana; Ni Nyoman Ratini; I Made Yuliara; I Wayan Supardi (Kappa Journal, 2024)
This study aims to determine the potential risk of thoracic organ cancer in CT Scan examinations using the Size-Specific Effective Dose (SSED) method, considering the importance of accurate radiation dose measurement to minimize the risk of cancer due to radiation exposure. The analysis was conducted on 30 female patients and 30 male patients in the adult category (17 - 45 years) at the Radiology Installation of Prof. Dr. I G. N. G. Ngoerah Hospital, Denpasar, using a descriptive quantitative approach with secondary data. The results showed that the Size-Specific Dose Estimate (SSDE) and SSED values ​​in female patients were 6.51 ± 0.70 mGy and 2.95 ± 0.48 mSv, respectively, while in male patients they were 6.38 ± 0.49 mGy and 2.27 ± 0.26 mSv. The risk of cancer in female patients is estimated at 0.016% and in male patients it is 0.012%. The Anova test showed a significant difference between the dose values ​​of the SSDE and SSED methods, which was caused by SSED only considering the dose of organs covered in the CT Scan image. However, the t-test showed that the doses from both methods did not exceed the BAPETEN standard No. 8 of 2011, so that the thoracic CT Scan examination in this Installation is safe and feasible to use.